(untitled) (Journal of Pakistan Orthopaedic Association, 2013)
Background: Most traumatic injuries to the tibia are caused by motor cycle or automobile accidents. Motor cycle related tibial injuries have high incidence of skin and soft tissues loss. To decrease this burden, spectrum of activities is needed, including injury surveillance, injury prevention and improvement in the care of wound e.g. by use of fasciocutaneous flaps. Objective: To, â€œEvaluate the incidence of open tibial fractures (Gustilo type III-B), its management by fasciocutaneous flaps and preventionâ€. Patients and Methods: This study was a prospective cohort study conducted in the orthopedic unit of Sheikh Zayed Medical College Rahim yar Khan from july 2008 to June 2009. All those patients who had skin loss over the tibia with intact distal neurovascular status along with ample normal surrounding skin were included in the study. The data was collected regarding age, sex, size of the wound, site of the wound and level of fracture mode of injury and use of any preventive/protective measures. Results: There were 1483 patients who had under gone surgery in ortho unit. Among these, twenty cases had open tibial fractures that needed fascioucutaneous flaps. Among these, there were 19(95%) males and one (5%) female. Twelve (60%) flaps were proximally based, two (10%) transversally based and six (30%) distally based. Eleven (55%) flaps were between 6cm to 8cm. Survival rate was 100%. Complications were noted in 9(45%) patients. Conclusion: This study has proven of the fasciocutaneous flaps. Key words: Trauma. Open tibial fractures. Fasciocutaneous flaps.